The Infinite Woman : Curated by Alona Pardo - Pardo, Alona; Le Squer, Kévin (s.l. : Editions Dilecta et Fondation Carmignac, 2024)
ALDRIDGE Miles ;AMER Ghada ; ANGER Kenneth ; ARMITAGE Michael ; BALL Sarah ; BENGOLEA Cecilia ; BLANC Mireille ; BOTTICELLI Sandro ; BOURGEOIS Louise ; BREITZ Candice ; CHICAGO Judy ; CURRIN John ; CURTISS Julie ; DE KOONING Willem ; DUMAS Marlène ; EBINAMA Chioma ; EDELSON Mary Beth ; EMIN Tracey ; GANESH Chitra ; GLYNN Nash ; GREVEN Vivian ; GUTIERREZ Martine ; HENROT Camille ; HOLLOWELL Loie ; HSU Tishan ; HUJAR Peter ; IANNONE Dorothy ; KAHRAMAN Hayv ; KEOGH Caitlin ; KOGELNIK Kiki ; KRISTALOVA Klara ; LEE Bul ; LEVINE Sherrie ; LICHTENSTEIN Roy ; McGURN France-Lise ; MITSOLA Sofia ; MUHOLI Zanele ; MUTU Wangechi ; OFILI Chris ; ORLAN ORUPABO Frida ; OTHONIEL Jean-Michel ; PERACH Anna ; PICASSO Pablo ; PIERRE Naudline ; PRINCE Richard ; PROUDFOOT Paloma ; PROUVOST Laure ; QUARLES Christina ; RUFF Thomas ; SAVILLE Jenny ; SCHIELE Egon ; SELF Tschabalala ; SIKANDER Shahzia ; SIN WAI KIN SINGER Avery ; SMITH Kiki STOLLER Jessica ; SZAPOCZNIKOW Alina TOMPKINS Betty ; TROCKEL Rosemarie ; URSUTA Andra ; VERBOOM Marion ; XIA Shafei ; YUSKAVAGE Lisa ; ZANGEWA Billie
The Infinite Woman, Paris, Fondation Carmignac, 27 April - 3 November 2024
boek